The effects of rider size and saddle fit for horse and rider on forces and pressure distribution under saddles: A pilot study. (9th April 2019) - Roost, L.; Ellis, A. D.; Morris, C.; Bondi, A.; Gandy, E. A.; Harris, P.; Dyson, S.
Summary: There is limited scientific evidence concerning the effect of rider weight on pressures under the saddle and equine performance. The objective of this prospective, crossover, randomised trial was to assess pressure distribution and magnitude in horses ridden by four riders of similar ability but differing in bodyweight and height. Six horses in regular work were ridden by four riders (rider bodyweight: horse body weight percentage > 10 ≤ 12 [L = Light], > 12 ≤ 15 [M = Moderate], > 15 ≤ 18 [H = Heavy] and > 20 [VH = Very Heavy]), performing a purpose‐designed dressage test (30 min). The test was abandoned for ≥ grade 3/8 lameness or ≥ 10 behavioural markers (assessed in real‐time). A calibrated force mat (Pliance) was used to record pressures under the saddle in walk, trot and canter on left and right reins. Rider position was assessed. All 13 H and VH tests and one of 12 M rider tests were abandoned (lameness, n  =  12; behaviour, n  =  1). At walk, the seat of rider VH extended beyond the cantle of the saddle; rider H sat on the cantle of the saddle. At trot and canter the heels of rider VH were consistently cranial to the tubera coxae and shoulders. Pressures were significantly higher under the caudal aspect of the saddle compared with cranially for rider VH in walk (P<0.05, ANOVA, Bonferroni). At rising trot pressures were higher cranially for riders L, M and H (P<0.05, ANOVA, Bonferroni), but were similar cranially and caudally for rider VH. The highest maximum peak pressure was recorded for rider VH in canter. A limitation was that speed can alter pressure measurements, but was not controlled or recorded. We concluded that there were differences in magnitude and distribution of pressures among the four riders according to their size, which may have contributed to the development of musculoskeletal pain. This may also have been influenced by saddle fit for riders and their positions.